Alleviation of methyl isocyanate−induced airway obstruction and mortality by tissue plasminogen activator. Issue 1 (31st March 2020) - Nick, Heidi J.; Rioux, Jacqueline S.; Veress, Livia A.; Bratcher, Preston E.; Bloomquist, Leslie A.; Anantharam, Poojya; Croutch, Claire R.; Tuttle, Richard S.; Peters, Eric; Sosna, William; White, Carl W.
Abstract: Methyl isocyanate (MIC, "Bhopal agent") is a highly reactive, toxic industrial chemical. Inhalation of high levels (500–1000 ppm) of MIC vapor is almost uniformly fatal. No therapeutic interventions other than supportive care have been described that can delay the onset of illness or death due to MIC. Recently, we found that inhalation of MIC caused the appearance of activated tissue factor in circulation with subsequent activation of the coagulation cascade. Herein, we report that MIC exposure (500 ppm for 30 min, nose‐only) caused deposition of fibrin‐rich casts in the conducting airways resulting in respiratory failure and death within 24 h in a rat model (LC90−100 ). We thus investigated the effect of airway delivery of the fibrinolytic agent tissue plasminogen activator (tPA) on mortality and morbidity in this model. Intratracheal administration of tPA was initiated 11 h post MIC exposure and repeated every 4 h for the duration of the study. Treatment with tPA afforded nearly 60% survival at 24 h post MIC exposure and was associated with decreased airway fibrin casts, stabilization of hypoxemia and respiratory distress, and improved acidosis. This work supports the potential of airway‐delivered tPA therapy as a useful countermeasure in stabilizing victims of high‐level MIC exposure. Abstract : Our study demonstrates that airway‐delivered tPA provided partial protection against mortality, and substantially decreased airway obstruction in an acutely lethal model of MIC inhalation exposure. This approach could be useful for airway clearance in acute therapy of MIC inhalation−induced respiratory distress. Furthermore, a similar therapeutic regimen may potentially alleviate lung injuries due to other isocyanates or diisocyanates, thereby expanding its clinical importance.